The model of Community Empowerment Participation in Tourism Village Management to Support Sustainable Economy in the Post Covid-19 Era - Mardiatul Jannah; Mirandha Ariesca Riana; A. Nurul Suci Amaliah; St. Aisyah (Institute of Computer Science (IOCS), 2022)
Tourism is one of the sectors that is expected to be able and contribute to boosting the economy after the Covid-19. One of the most potential in the Indonesian tourism industry is the development of tourism village-based tourism. In the management of tourism villages in Indonesia, the role of empowered community groups and empowerment models plays an important role. This study aims to see how the participation model of community empowerment in managing a tourist village by taking the object of one of the tourist villages tends to be consistent. The novelty in this research lies in the model that will be described in the research results, where the model shows a image of community participation in empowerment, especially in the Rammang-rammang Tourism Village, Maros Regency. This research also aims to assist in uncovering business potentials that can be developed by the community as an effort to support a sustainable economy, especially in the post-covid-19 era. This study uses a descriptive qualitative approach with a data analysis model using a simultaneous stage analysis model or the 6P model. The results of this study indicate that there is a good synergy between the surrounding community as tourism village managers, the government, the private sector and educational institutions in advancing the Rammang-rammang tourist village, while the empowerment model found is in the form of community empowerment through Kelompok Sadar Wisata (Pokdarwis) and the role of BUMDES is still need to be maximized in managing the existing business potential..